An updated species checklist for free-living marine nematodes from the world’s largest mangrove ecosystem, Sundarbans - Ansari, Kapuli Gani Mohamed Thameemul; Bhadury, Punyasloke (Zootaxa, 2017)
The present study provides an updated species checklist for free-living marine nematode species from the world’s largest contiguous mangrove ecosystem, the Sundarbans (India and Bangladesh). The species checklist includes information available from Sundarbans from the 1950s to the present (2016), using the most recent taxonomic classification of nematodes. The species list contains 179 species in 84 genera and 29 families. Four families, Xyalidae (22 species), Linhomoeidae (18 species), Desmodoridae (16 species) and Chromadoridae (15 species) were most speciose. The genera Halalaimus (9 species), Sabatieria and Daptonema (8 species each) were most species rich; 50 genera were represented by just a single species. Six species are new distributional records for Indian waters. The species checklist is the most extensive list of free-living marine nematodes from the Sundarbans mangrove ecosystem to date and provides a framework for studying biogeography of free-living marine nematodes from mangrove ecosystems globally.